Crystal structure of [1-(2, 6-diisopropylphenyl)-2, 4-bis(dimethylamino)-5-trimethylsilyl-1, 3, 5-triazapentadienyl-κ2N1, N5](triphenylphosphane-κP)copper(I). (March 2015) - Li, Feiguang; Yan, Lei; Tong, Hongbo; Zhou, Meisu
No abstract available